Limites e possibilidades da formação continuada de professores da educação profissional - Celistre, Sinara Sant’Anna (2015)
In the Brazilian education scnario, Technical and Vocational Education and Training (TVET) has made an effective contribution towards the entrance of new generations in the labor market. Accordingly, investing in the further qualification of teachers working in that field is a strategy that will enable education to achieve its goals. That fact has aroused questioning of the effectiveness of graduate specialization courses dedicated to the in-service, further qualification of teachers. To answer the question this research set out to assess the limits and possibilities of such a program for teachers in that field and the effects of the program on their teaching practices. The case study method of investigation was adopted because it allows for an understanding of the more complex social phenomena. Participants included teachers, students, and pedagogical coordinators of a private education institution. The study conclusions were that: rather than just learning more about teaching methods and techniques, TVET teachers need to appropriate components that are essential to provide them with an understanding of the complexity of the educator’s task. Although teaching and learning are distinct from one another, when teaching does not lead to learning, it becomes an innocuous act; lifelong learning and qualification is a bid to decipher theory in order to organize and support it, reformulate it and, if necessary, refute it, dislodging the usual perceptions of education; and, an educational process that fails to ensure that the teacher has the components needed to bring about change autonomously and securely is necessarily flawed in its intent and results; much of what teachers do and achieve stems from what they believe in individually. Thus, understanding should be followed by acceptance because the mere mechanical repetition of practices generates mistaken interpretations. In-service evaluation of teachers in their normal classroom activities is indispensable for the purpose of following up on the results of educative actions which should lead to better teaching and increased learning on the part of students. When it disseminates innovations to its students, the institution must realize that, even though they have undergone the same educational process, they will have different perceptions individually and take different lengths of time to put into practice, or not, the proposed changes. Pedagogical theory and practice form an inseparable unit that should be the nucleus that structures the teacher’s education; the school and its web should be the object of study in order to achieve an understanding of the real needs of those that actually materialize the educational actions. The considerable distance between educational reform proposals and their effective materialization suggests that there is a problem associated to the illusory nature of some projects designed bring about changes. At the same time as the teachers’ reflective capacity is being expanded, it is essential to think through the qualifying process they undergo, taking as the starting point, the practical demands, that is, the real circumstances lived out in social contexts and in the organizations where teaching takes place. Educational proposals must be supported on the basis of a systemic vision taking into account the connections that exist between knowledge and know how. The decisive elements that actually brought about changes in the discourse and practices of TEVT teachers that took part in the graduate specialization course were the establishment of the relations between the knowledge acquired and the reality of the daily round of their teaching activity, and the existence of the will to bring about change in concepts and behaviors and of a propitious environment for change.